Modal Sosial Berperan dalam Pengembangan Desa Wisata Berbasis Kearifan Lokal Di Pasar Terapung Lok Baintan - Widaty, Cucu; Apriati, Yuli; Gea, Yarni Ester; Lase, Four Steven; Angga, M.; Fiqri, Fiqri (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
The development of a tourism village in the Lok Baintan Floating Market still faces various challenges. Problems such as the community's low understanding of the concept of village tourism, limited innovation in tourism product development, and a lack of coordination between stakeholders are obstacles in destination management. Social capital is a key element that determines the dynamics of village development. The purpose of this study is to analyze the supporting and inhibiting factors in the utilization of social capital. This study uses a qualitative approach with a case study method, data collection through participant observation, in-depth interviews, documentation, and focus group discussions. The results show that supporting factors include the strength of local values that are still maintained. These values form trust, as well as adaptation to technology. Obstacles include individualism, language barriers, low involvement of the younger generation, natural conditions, and limited infrastructure and regulations.